The molecular structure features-immune stimulatory activity of arabinoxylans derived from the pentosan faction of wheat flour. (March 2015) - Li, Weili; Zhang, Shuangyue; Smith, Chris
Abstract: Recently, the immune stimulation properties of cereal arabinoxylans (AX) have been reported. The aims of this study were to identify the molecular features and potential immune stimulation activities of AX and enzymatic modified arabinoxylan (AXE) from the pentosan fraction of wheat flour. The results of molecular characterization of AX and AXE show that AXE contains a larger portion (85.7%) of low Mw arabinoxylans (≤25 kDa) and has a higher degree of branch substitution (0.81 ± 0.01) compared to AX (49.5% and 0.62 ± 0.02). In in vitro testing, the ability of AX and AXE to stimulate immune cells, as measured by NO2 − production by U937 cells and IL-8 secretion by Caco-2 cells were found to be dose–dependent in the range tested (100–5000 μg/mL p  ≤ 0.05). AXE showed a greater activity at each concentration (100–5000 μg/mML) than AX ( p  ≤ 0.05). In conclusion, the greater immune stimulating activity of AXE may be associated with its low Mw (≤25 kDa) and a higher degree of branch substitution (0.81 ± 0.01). Highlights: Extract and modify the arabinoxylans from the pentosan fraction of wheat flour. Characterise the molecular features of extracted and modified arabinoxylans. Test the immune modulating properties of arabinoxylans in in vitro studies.